1995
DOI: 10.1002/mrd.1080400113
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous substrate for energy metabolism and ultrastructural correlates in spermatozoa of the sea urchin Diadema setosum

Abstract: Energy metabolism in spermatozoa of the sea urchin Diadema setosum of the order Diadematoida was examined. The spermatozoa contained not only several kinds of phospholipids and cholesterol, but also triglyceride (TG). Glycogen and glucose were present at extremely low levels. Following dilution of dry sperm and incubation in seawater, the TG content decreased rapidly. Other lipids, however, remained at constant levels, except for a slight increase in the level of free fatty acid. High lipase activity was demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…As with the two regular urchins from NZ, a deep centriolar fossa is described in other regular urchins such as Arbacia punctulata ( Lamarck 1816) (Franklin ), S. droebachiensis (Afzelius & Murray ) and the diadematoid Diadema setosum ( Leske 1778) Mita et al. ). In comparison, the shallow centriolar fossa in the irregular urchins F. zelandiae and E. cordatum is a characteristic shared with other irregular species such as Clypeaster japonicus ( Döderlein 1885) (Mita & Nakamura ) and Echinarachnius parma ( Lamarck 1816) (Summers & Hylander ).…”
Section: Discussionmentioning
confidence: 88%
“…As with the two regular urchins from NZ, a deep centriolar fossa is described in other regular urchins such as Arbacia punctulata ( Lamarck 1816) (Franklin ), S. droebachiensis (Afzelius & Murray ) and the diadematoid Diadema setosum ( Leske 1778) Mita et al. ). In comparison, the shallow centriolar fossa in the irregular urchins F. zelandiae and E. cordatum is a characteristic shared with other irregular species such as Clypeaster japonicus ( Döderlein 1885) (Mita & Nakamura ) and Echinarachnius parma ( Lamarck 1816) (Summers & Hylander ).…”
Section: Discussionmentioning
confidence: 88%
“…), two features of sperm morphology that may influence sperm performance (SeGall and Lennarz ; Mita et al ). The volume of mitochondria and their associated energy stores have been demonstrated to be important for long‐term activity of sperm in broadcast spawning invertebrates (Afzelius and Mohri ; Mita et al ), suggesting that sperm with larger mitochondrial packets may live longer and thereby increase their chance of participating in fertilizations. Larger acrosomes could also confer a fertilization advantage.…”
Section: Discussionmentioning
confidence: 99%
“…Sperm longevity is often hypothesized to be important for fertilization success, especially under sperm-limited conditions when the average time until sperm-egg encounters is low (Levitan 1993;Williams and Bentley 2002;Johnson and Yund 2004;Pizzari et al 2008). Although the morphological correlates of longevity are often unclear, there is some evidence that longevity may be related to energy reserves and associated storage structures such as mitochondria (Afzelius and Mohri 1966;Mita et al 1995).…”
mentioning
confidence: 99%
“…Fatty acids, also stored in lipid globules at the middlepieces, have been shown to be the main source of energy for the spermatozoa of several sea urchin species (Mita, 1991;Mita et al, 1995). It has also been shown that fatty acids are the energy source for mammalian spermatozoa (Lardy and Phillips, 1941).…”
Section: Kolmer Et Almentioning
confidence: 98%